Impaired Antioxidant Defence Status Is Associated With Metabolic-Inflammatory Risk Factors in Preterm Children With Extrauterine Growth Restriction: The BIORICA Cohort Study - Ordóñez-Díaz, María Dolores; Gil-Campos, Mercedes; Flores-Rojas, Katherine; Muñoz-Villanueva, María Carmen; Mesa, María Dolores; de la Torre-Aguilar, María José; Gil, Ángel; Pérez-Navero, Juan Luis (Frontiers in Nutrition, 2021)
Introduction: An impaired antioxidant status has been described during fetal growth restriction (FGR). Similarly, the antioxidant defense system can be compromised in preterm children with extrauterine growth restriction (EUGR). The aim of this prospective study was to evaluate the antioxidant status in prepubertal children with a history of prematurity without FGR, with and without EUGR, compared to a healthy group. Methods: In total, 211 children were recruited and classified into three groups: 38 with a history of prematurity and EUGR; 50 with a history of prematurity and adequate extrauterine growth (AEUG); and 123 control children born at term. Catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione reductase (GR) activities were assessed in lysed erythrocytes with spectrophotometric methods. Plasma levels of the antioxidants α-tocopherol, retinol and β-carotene were determined through solvent extraction and ultra-high-pressure liquid chromatography coupled to mass spectrometry. Results: Children with the antecedent of EUGR and prematurity had lower CAT activity than the other two groups and lower GPx activity than the control children. Lower SOD, GPx and GR activities were observed in the AEUG group compared to the controls. However, higher concentrations of α-tocopherol and β-carotene were found in the EUGR group compared to the other groups; retinol levels were also higher in EUGR than in AEUG children. In EUGR and AEUG children, enzymatic antioxidant activities and plasma antioxidants were associated with metabolic syndrome components and pro-inflammatory biomarkers. Conclusions: This study reveals, for the first time, that the EUGR condition and prematurity appear to be linked to an impairment of the antioxidant defense status, which might condition an increased risk of adverse metabolic outcomes later in life.